Dynamic covalent cross-linking material based on thermoplastic polymer as well as preparation method and application of dynamic covalent cross-linking material

By forming a dynamic covalent crosslinking network of ester exchange in thermoplastic polymers, the problems of deformation, creep and performance degradation of traditional thermoplastic polymers under high temperature or long-term load are solved, their thermal stability and mechanical strength are significantly improved, and the high value and industrial production of materials are achieved.

CN119529199AActive Publication Date: 2025-02-28BEIJING UNIV OF CHEM TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411841144.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-28
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Traditional thermoplastic polymers are prone to deformation, creep and performance degradation under high temperatures or long-term loads, which limits their application.

Method used

By melt blending thermoplastic polymers, acid anhydrides and initiators, the amount of grafting of the anhydride is increased, and the epoxy groups in the crosslinking agent react with the anhydride under the action of a catalyst to form a dynamic covalent crosslinking network of transesterification.

Benefits of technology

While not affecting the repeatable processing properties of thermoplastic polymers, it significantly improves its thermal stability and mechanical strength, realizes the high value of the material, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529199A_ABST
    Figure CN119529199A_ABST
Patent Text Reader

Abstract

The invention relates to a dynamic covalent cross-linking material based on a thermoplastic polymer and a preparation method and application thereof, and belongs to the technical field of polymer materials.The preparation method of the dynamic covalent cross-linking material comprises the following steps that S1, a mixture containing the thermoplastic polymer, an anhydride substance and an initiator is subjected to first melt blending, a melt blend is obtained; s2, uniformly mixing the melt blend, a cross-linking agent and a catalyst, and carrying out second melt blending to obtain a dynamic covalent cross-linking material based on the thermoplastic polymer; the cross-linking agent is a diglycidyl ether epoxide. The preparation method of the dynamic covalent cross-linking material provided by the invention is simple in process and short in preparation period, can be used for converting thermoplastic macromolecules and waste thermoplastic macromolecules into dynamic cross-linking materials with excellent mechanical, creep-resistant, heat-resistant and chemical solvent-resistant properties, realizes high value, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a dynamic covalent cross-linking material based on thermoplastic polymers, and a preparation method and application thereof. Background Art

[0002] Thermoplastic polymers are a type of polymer material that softens when heated and resolidifies after cooling. They have good processability and mechanical properties and are widely used in the fields of electronics, electrical, automotive, and medical. However, due to their linear molecular chain structure, the molecular chains mainly rely on physical forces such as chain entanglement or crystallization to maintain structural stability, which makes the mechanical strength, creep resistance, and thermal stability of thermoplastic polymers relatively limited compared to thermosetting polymers. Under high temperature or long-term load, traditional thermoplastic polymers are prone to deformation, creep, and performance degradation, which limits their application. Summary of the invention

[0003] In view of one or more technical problems existing in the prior art, the present invention provides a dynamic covalent cross-linked material based on thermoplastic polymers, a preparation method and application thereof. The preparation method of the dynamic covalent cross-linked material provided by the present invention has a simple process and a short preparation cycle. It can be used to convert thermoplastic polymers and waste thermoplastic polymers into dynamic cross-linked materials with excellent mechanical, creep resistance, heat resistance and chemical solvent resistance properties, thereby realizing their high value and being suitable for industrial production.

[0004] The present invention provides a method for preparing a dynamic covalent cross-linked material based on a thermoplastic polymer, the preparation method comprising the following steps:

[0005] S1. A mixture comprising a thermoplastic polymer, an anhydride substance, and an initiator is first melt-blended to obtain a melt blend;

[0006] S2: uniformly mixing the molten blend, the crosslinking agent and the catalyst, and performing a second melt blending to obtain a dynamic covalent crosslinking material based on a thermoplastic polymer; the crosslinking agent is a diglycidyl ether epoxide.

[0007] Preferably, the mass ratio of the acid anhydride substance to the thermoplastic polymer is 0.1 to 15:100;

[0008] The mass ratio of the initiator to the thermoplastic polymer is 0.01 to 1.5:100;

[0009] The mass ratio of the cross-linking agent to the thermoplastic polymer is 0.5 to 120:100; and / or

[0010] The mass ratio of the catalyst to the thermoplastic polymer is 0.02 to 5:100.

[0011] Preferably, the mixture further comprises an auxiliary agent; the auxiliary agent is one or more of α-methylstyrene, styrene, dimethylformamide, decene, ethyl benzoate, 2,2′-bipyridine, stearamide, dimethylacetamide, N,N-diethylcinnamic acid amide, N,N-dimethylacetamide, 3-(2-furan)acrylic acid, ethyl cinnamate, dimethylaniline, dilauryl thiodipropionate, trimethylolpropane triacrylate, 3-(2-furanyl)butyl acrylate, 3-(2-thienyl)butyl acrylate, 4,4-diaminodiphenylmethane, cashew nut shell oil, triallyl isocyanurate, and 1,2-polybutadiene.

[0012] Preferably, the mass ratio of the auxiliary agent to the thermoplastic polymer is 0.1 to 15:100.

[0013] Preferably, the thermoplastic polymer is one or more of acrylonitrile-butadiene-styrene copolymer, styrene-butadiene-styrene copolymer, styrene-ethylene-butylene-styrene copolymer, styrene-isoprene-styrene copolymer, ethylene-vinyl acetate copolymer, polyolefin elastomer, polyethylene, polypropylene and recycled materials thereof;

[0014] The acid anhydride substance is one or more of maleic anhydride, methyl isophthalic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, dimethyl maleic anhydride, methacrylic anhydride, itaconic anhydride, acrylic anhydride, trimellitic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride, tetrachlorophthalic anhydride, acrylic anhydride, methyltetrahydrophthalic anhydride, benzoic anhydride, 4-bromo-1,8-naphthalic anhydride, 1,8-naphthalic anhydride, 3-nitrophthalic anhydride, and tetrabromophthalic anhydride; and / or

[0015] The initiator is one or more of a peroxide initiator, an azo initiator, and N,N-dimethylamine; the peroxide initiator is preferably one or more of diisopropyl peroxide, dibenzoyl peroxide, di-tert-butyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, lauroyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, and dicyclohexyl peroxydicarbonate; the azo initiator is preferably one or more of azobisisobutyronitrile and azobisisoheptylonitrile.

[0016] Preferably, the bisglycidyl ether epoxide is one or more of ethylene glycol diglycidyl ether, bisphenol A diglycidyl ether, and resorcinol diglycidyl ether; and / or

[0017] The catalyst is one or more of zinc acetylacetonate, triazobicyclodecene and triphenylphosphine.

[0018] Preferably, the first melt blending temperature is 110 to 230° C., and the time is 7 to 15 min; and / or

[0019] The temperature of the second melt blending is 110-230° C., and the time is 7-15 minutes.

[0020] The present invention provides a dynamic covalent cross-linking material based on thermoplastic polymer in a second aspect, characterized in that it is prepared by the preparation method described in the first aspect.

[0021] The present invention provides, in a third aspect, an application of the dynamic covalent cross-linking material based on thermoplastic polymers described in the second aspect, which is applied to the preparation of thermoplastic polymer composite materials; the preparation method of the thermoplastic polymer composite material comprises: mixing the dynamic covalent cross-linking material with the thermoplastic polymer, performing a third melt blending, and obtaining the thermoplastic polymer composite material.

[0022] Preferably, the temperature of the third melt blending is 110-230° C., and the time is 7-15 min; and / or

[0023] The mass ratio of the dynamic covalent cross-linking material to the thermoplastic polymer is 5-70:30-95.

[0024] Compared with the prior art, the present invention has at least the following beneficial effects:

[0025] The present invention firstly melt-blends a thermoplastic polymer, an acid anhydride substance and an initiator, and under the action of the initiator, increases the grafting amount of the acid anhydride on the thermoplastic polymer, and then under the action of a catalyst, the epoxy group in the crosslinking agent reacts with the acid anhydride to generate an ester group and a hydroxyl group, thereby forming a dynamic covalent crosslinking network of ester exchange, which effectively improves the thermal stability and mechanical strength of the thermoplastic polymer without affecting the repeatable processing performance of the thermoplastic polymer.

[0026] The preparation method of the dynamic covalent cross-linked material provided by the present invention has a simple process and a short preparation cycle, and can be used to convert thermoplastic polymers and waste thermoplastic polymers into dynamic cross-linked materials with excellent mechanical, creep resistance, heat resistance, and chemical solvent resistance properties, thereby achieving high value and being suitable for industrial production.

[0027] The dynamic cross-linking network in the dynamic covalent cross-linking material provided by the present invention can give the polymer material higher thermal stability and mechanical strength without sacrificing its processability. It also allows the material to achieve topological rearrangement of the polymer network through reversible exchange reactions between different ester groups under light, heat or chemical stimulation, thereby achieving reshaping, repair and recycling, taking into account the dual requirements of durability and processability, and significantly enhancing the service life and stability of the material under extreme conditions.

[0028] The present invention melt-blends the dynamic covalent cross-linking material and the thermoplastic polymer to obtain a thermoplastic polymer composite material with excellent mechanical properties. Compared with the thermoplastic polymer raw material and the dynamic covalent cross-linking material, the thermoplastic polymer composite material has better mechanical properties and creep resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 It is an infrared spectrum diagram of the effect of the auxiliary agent of the present invention on the grafting amount of the reactive reagent (acid anhydride substance);

[0031] Figure 2 It is a storage modulus curve diagram of the dynamic covalent cross-linked material based on ABS recycled material and ABS recycled material provided in Example 4 of the present invention;

[0032] Figure 3 is a storage modulus curve diagram of a dynamic covalent cross-linked material based on a polypropylene material and a polypropylene material provided in Example 8 of the present invention;

[0033] Figure 4 is a stress-strain curve diagram of the thermoplastic polymer composite material and ABS provided in Example 12 of the present invention;

[0034] Figure 5 It is a stress-strain curve diagram of the thermoplastic polymer composite material and polypropylene material provided in Example 13 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] The present invention provides a method for preparing a dynamic covalent cross-linked material based on a thermoplastic polymer, the preparation method comprising the following steps:

[0037] S1. A mixture comprising a thermoplastic polymer, an anhydride substance, and an initiator is first melt-blended to obtain a melt blend;

[0038] S2: uniformly mixing the molten blend, the crosslinking agent and the catalyst, and performing a second melt blending to obtain a dynamic covalent crosslinking material based on a thermoplastic polymer; the crosslinking agent is a diglycidyl ether epoxide.

[0039] The present invention firstly melt-blends a thermoplastic polymer, an acid anhydride substance and an initiator, and under the action of the initiator, increases the grafting amount of the acid anhydride on the thermoplastic polymer, and then under the action of a catalyst, the epoxy group in the crosslinking agent reacts with the acid anhydride to generate an ester group and a hydroxyl group, thereby forming a dynamic covalent crosslinking network of ester exchange, which effectively improves the thermal stability and mechanical strength of the thermoplastic polymer without affecting the repeatable processing performance of the thermoplastic polymer.

[0040] The preparation method of the dynamic covalent cross-linked material provided by the present invention has a simple process and a short preparation cycle, and can be used to convert thermoplastic polymers and waste thermoplastic polymers into dynamic cross-linked materials with excellent mechanical, creep resistance, heat resistance, and chemical solvent resistance properties, thereby achieving high value and being suitable for industrial production.

[0041] According to some preferred embodiments, the mass ratio of the acid anhydride substance to the thermoplastic polymer is 0.1 to 15:100 (for example, it can be 0.1:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100 or 15:100).

[0042] According to some preferred embodiments, the mass ratio of the initiator to the thermoplastic polymer is 0.01 to 1.5:100 (for example, it can be 0.01:100, 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100, 1.0:100, 1.1:100, 1.2:100, 1.3:100, 1.4:100 or 1.5:100).

[0043] The present invention controls the amount of thermoplastic polymer, anhydride substance, and initiator within the above range to ensure the grafting amount of reactive agent (anhydride substance), and then utilizes the anhydride to react with the epoxy group in the cross-linking agent to generate ester group and hydroxyl group, forming a dynamic covalent cross-linking system of ester exchange, and then obtaining a high-strength dynamic covalent cross-linking material. The inventors found that if the amount of initiator is too little, the grafting amount of reactive agent (anhydride substance) will decrease, so that the strength of the final material will decrease; if the amount of initiator is too much, it will cause the degradation of thermoplastic polymer, so that the Young's modulus of the obtained dynamic covalent cross-linking material will decrease, that is, the strength will decrease.

[0044] According to some preferred embodiments, the mass ratio of the crosslinking agent to the thermoplastic polymer is 0.5 to 120:100 (for example, it can be 0.5:100, 0.8:100, 10:100, 20:100, 30:100, 40:100, 50:100, 60:100, 70:100, 80:100, 90:100, 100:100, 110:100 or 120:100).

[0045] The mass ratio of the catalyst to the thermoplastic polymer is 0.02 to 5:100 (for example, 0.02:100, 0.05:100, 0.1:100, 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100 or 5:100).

[0046] According to some preferred embodiments, the mixture further includes an auxiliary agent; the auxiliary agent is one or more of α-methylstyrene, styrene, dimethylformamide, decene, ethyl benzoate, 2,2′-bipyridine, stearamide, dimethylacetamide, N,N-diethylcinnamic acid amide, N,N-dimethylacetamide, 3-(2-furan)acrylic acid, ethyl cinnamate, dimethylaniline, dilauryl thiodipropionate, trimethylolpropane triacrylate, 3-(2-furanyl)butyl acrylate, 3-(2-thienyl)butyl acrylate, 4,4-diaminediphenylmethane, cashew nut shell oil, triallyl isocyanurate, and 1,2-polybutadiene.

[0047] According to some preferred embodiments, the mass ratio of the auxiliary agent to the thermoplastic polymer is 0.1 to 15:100 (for example, it can be 0.1:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100 or 15:100).

[0048] The present invention further increases the grafting amount of the reactive reagent (anhydride substance) by introducing an auxiliary agent into the reaction system, thereby further increasing the strength of the material. The inventors have found that if the amount of the auxiliary agent is too much, the small molecules in the obtained dynamic covalent cross-linked material system will increase, which may overflow to the surface of the material during the subsequent use of the material, affecting the use effect of the material, and also causing a decrease in the strength of the dynamic covalent cross-linked material. Therefore, the present invention controls the amount of the auxiliary agent within the above range.

[0049] Taking styrene as an example, the present invention explores the effect of the additive on the grafting amount of the reactive reagent (anhydride substance). The infrared spectrum is as follows: Figure 1 As shown, it should be noted that Figure 1 rABS is ABS recycled material, rABS-MA is without additives, and rABS-MA-St is with additives; wavelength is 1780cm -1 The infrared absorption peak of maleic anhydride is at , and the larger the peak value, the more maleic anhydride is grafted onto ABS. Figure 1 It can be seen that ABS recycled material is 1780cm -1 There is no absorption peak at the position. The carbonyl absorption peak of rABS-MA-St prepared after adding additives is larger than that of rABS-MA prepared without adding additives. It can be seen that adding additives is beneficial to improving the grafting rate of acid anhydride.

[0050] According to some preferred embodiments, the thermoplastic polymer is one or more of acrylonitrile-butadiene-styrene copolymer (ABS), styrene-butadiene-styrene copolymer (SBS), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-isoprene-styrene copolymer (SIS), ethylene-vinyl acetate copolymer, polyolefin elastomer, polyethylene (PE), polypropylene (PP) and their recycled materials. The thermoplastic polymer material is at least one of a block and a granular material. Among them, polyethylene (PE) includes at least one of high-density polyethylene, low-density polyethylene, and linear low-density polyethylene.

[0051] According to some preferred embodiments, the acid anhydride substance is one or more of maleic anhydride, methyl isophthalic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, dimethylmaleic anhydride, methacrylic anhydride, itaconic anhydride, acrylic anhydride, trimellitic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride, tetrachlorophthalic anhydride, acrylic anhydride, methyltetrahydrophthalic anhydride, benzoic anhydride, 4-bromo-1,8-naphthalene dicarboxylic anhydride, 1,8-naphthalene dicarboxylic anhydride, 3-nitrophthalic anhydride, and tetrabromophthalic anhydride.

[0052] According to some preferred embodiments, the initiator is one or more of a peroxide initiator, an azo initiator, and N,N-dimethylamine; the peroxide initiator is preferably diisopropyl peroxide, dibenzoyl peroxide, di-tert-butyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, lauroyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, and one or more of dicyclohexyl peroxydicarbonate; the azo initiator is preferably azobisisobutyronitrile and azobisisoheptylonitrile.

[0053] According to some preferred embodiments, the bisglycidyl ether epoxide is one or more of ethylene glycol diglycidyl ether, bisphenol A diglycidyl ether, and resorcinol diglycidyl ether. The present invention selects bisglycidyl ether epoxide as a crosslinking agent, and utilizes the epoxy group in the bisglycidyl ether epoxide to react with anhydride to generate an ester group and a hydroxyl group, thereby forming a dynamic covalent crosslinking network of ester exchange, thereby obtaining a dynamic covalent crosslinking material.

[0054] According to some preferred embodiments, the catalyst is one or more of zinc acetylacetonate (Zn(acac)2), triazobicyclodecene (TBD), and triphenylphosphine (PPh3).

[0055] According to some preferred embodiments, the temperature of the first melt blending is 110-230°C (for example, it can be 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C or 230°C), and the time is 7-15 min (for example, it can be 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min).

[0056] According to some preferred embodiments, the temperature of the second melt blending is 110-230°C (for example, it can be 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C or 230°C), and the time is 7-15 min (for example, it can be 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min).

[0057] The present invention provides a dynamic covalent cross-linking material based on thermoplastic polymer in a second aspect, characterized in that it is prepared by the preparation method described in the first aspect.

[0058] The dynamic cross-linking network in the dynamic covalent cross-linking material provided by the present invention can give the polymer material higher thermal stability and mechanical strength without sacrificing its processability. It also allows the material to achieve topological rearrangement of the polymer network through reversible exchange reactions between different ester groups under light, heat or chemical stimulation, thereby achieving reshaping, repair and recycling, taking into account the dual requirements of durability and processability, and significantly enhancing the service life and stability of the material under extreme conditions.

[0059] The present invention provides, in a third aspect, an application of the dynamic covalent cross-linking material based on thermoplastic polymers described in the second aspect, which is applied to the preparation of thermoplastic polymer composite materials; the preparation method of the thermoplastic polymer composite material comprises: mixing the dynamic covalent cross-linking material with the thermoplastic polymer, performing a third melt blending, and obtaining the thermoplastic polymer composite material.

[0060] The present invention melt-blends the dynamic covalent cross-linking material and the thermoplastic polymer to obtain a thermoplastic polymer composite material with excellent mechanical properties. Compared with the thermoplastic polymer raw material and the dynamic covalent cross-linking material, the thermoplastic polymer composite material has better mechanical properties and creep resistance.

[0061] It should be noted that, in the process of mixing the dynamic covalent crosslinking material with the thermoplastic polymer, the thermoplastic polymer selected can be the same as or different from the thermoplastic polymer used to prepare the dynamic covalent crosslinking material.

[0062] According to some preferred embodiments, the third melt blending has a temperature of 110 to 230° C. (e.g., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., 190° C., 200° C., 210° C., 220° C., or 230° C.), and a time of 7 to 15 min (e.g., 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, or 15 min); and / or

[0063] The mass ratio of the dynamic covalent crosslinking material to the thermoplastic polymer is 5-70:30-95 (for example, 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 40:60, 50:50, 60:40 or 70:30), preferably 5-30:70-95.

[0064] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.

[0065] It should be noted that the testing methods for the performance data of the dynamic covalent cross-linked materials and thermoplastic polymer composite materials provided in the embodiments and comparative examples of the present invention are as follows:

[0066] Dumbbell-shaped specimens were prepared on a hot press, and the mechanical properties of the prepared specimens were tested using a universal material testing machine to obtain the Young's modulus, yield strength and elongation at break of the prepared specimens.

[0067] Preparation of Dynamic Covalently Cross-linked Materials Based on Thermoplastic Polymers

[0068] Example 1

[0069] The recycled ABS material, maleic anhydride, and diisopropylbenzene peroxide were uniformly mixed in a mass ratio of 100:3:0.25, and then melt-blended in an internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 8 minutes. Then, ethylene glycol diglycidyl ether and zinc acetylacetonate were added to the internal mixer at a mass ratio of 10:0.5:100 to the recycled ABS material, and the mixture was further blended in the internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 10 minutes to obtain a dynamic covalent cross-linked material based on recycled ABS material.

[0070] Example 2

[0071] The polyethylene material, maleic anhydride, diisopropylbenzene peroxide and styrene were uniformly mixed in a mass ratio of 100:3:0.25, and then melt-blended in an internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 8 minutes. Then, ethylene glycol diglycidyl ether and zinc acetylacetonate were added to the internal mixer at a mass ratio of 10:0.5:100 to the recycled ABS material, and the mixture was further blended in the internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 10 minutes to obtain a dynamic covalent cross-linked material based on the polyethylene material.

[0072] Example 3

[0073] The polypropylene material, maleic anhydride and diisopropylbenzene peroxide were uniformly mixed in a mass ratio of 100:3:0.25, and then melt-blended in an internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 8 minutes. Then, ethylene glycol diglycidyl ether and zinc acetylacetonate were added to the internal mixer at a mass ratio of 10:0.5:100 with the recycled ABS material, and the mixture was further blended in the internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 10 minutes to obtain a dynamic covalent cross-linked material based on the polypropylene material.

[0074] Example 4

[0075] The recycled ABS material, maleic anhydride, diisopropylbenzene peroxide and styrene were uniformly mixed in a mass ratio of 100:3:0.25:3, and then melt-blended in an internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 8 minutes. Then, ethylene glycol diglycidyl ether and zinc acetylacetonate were added to the internal mixer at a mass ratio of 10:0.5:100 to the recycled ABS material, and the mixture was further blended in the internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 10 minutes to obtain a dynamic covalent cross-linked material based on recycled ABS material.

[0076] Depend on Figure 2 It can be seen that the dynamic covalent cross-linked material (rABS-v) based on ABS recycled material prepared in Example 4 has a rubber platform compared with ABS recycled material (rABS), which shows that the prepared rABS-v forms cross-links.

[0077] Example 5

[0078] The recycled ABS material, maleic anhydride, diisopropylbenzene peroxide and styrene were uniformly mixed in a mass ratio of 100:0.1:0.01:0.1, and then melt-blended in an internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 8 minutes. Then, ethylene glycol diglycidyl ether and zinc acetylacetonate were added to the internal mixer at a mass ratio of 0.8:0.02:100 to the recycled ABS material, and the mixture was further blended in the internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 10 minutes to obtain a dynamic covalent cross-linked material based on recycled ABS material.

[0079] Example 6

[0080] The recycled ABS material, maleic anhydride, diisopropylbenzene peroxide and styrene were mixed uniformly in a mass ratio of 100:15:1.5:15, and then melt-blended in an internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 8 minutes. Then, ethylene glycol diglycidyl ether and zinc acetylacetonate were added to the internal mixer at a mass ratio of 120:3:100 to the recycled ABS material, and the mixture was further blended in the internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 10 minutes to obtain a dynamic covalent cross-linked material based on recycled ABS material.

[0081] Example 7

[0082] The polyethylene material, maleic anhydride, diisopropylbenzene peroxide and styrene were uniformly mixed in a mass ratio of 100:3:0.25:3, and then melt-blended in an internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 8 minutes. Then, ethylene glycol diglycidyl ether and zinc acetylacetonate were added to the internal mixer at a mass ratio of 10:0.5:100 with the recycled ABS material, and the mixture was further blended in the internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 10 minutes to obtain a dynamic covalent cross-linked material based on the polyethylene material.

[0083] Example 8

[0084] The polypropylene material, maleic anhydride, diisopropylbenzene peroxide and styrene were uniformly mixed in a mass ratio of 100:3:0.25:3, and then melt-blended in an internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 8 minutes. Then, ethylene glycol diglycidyl ether and zinc acetylacetonate were added to the internal mixer at a mass ratio of 10:0.5:100 to the recycled ABS material, and the mixture was further blended in the internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 10 minutes to obtain a dynamic covalent cross-linked material based on the polypropylene material.

[0085] Depend on Figure 3 It can be seen that the dynamic covalent cross-linked material (PP-v) based on polypropylene material prepared in Example 8 has a rubber platform compared with the polypropylene material (PP), and it can be seen that the prepared PP-v forms cross-links.

[0086] Comparative Example 1

[0087] The method is basically the same as Example 4, except that the mass ratio of the recovered ABS material, maleic anhydride, dicumyl peroxide and styrene is 100:3:0.005:3.

[0088] Comparative Example 2

[0089] The method is basically the same as Example 4, except that the mass ratio of the recovered ABS material, maleic anhydride, dicumyl peroxide and styrene is 100:3:6:3.

[0090] Comparative Example 3

[0091] The method is basically the same as Example 4, except that the mass ratio of the recovered ABS material, maleic anhydride, dicumyl peroxide and styrene is 100:3:0.25:30.

[0092] Comparative Example 4

[0093] The method is basically the same as Example 4, except that the mass ratio of the recovered ABS material, maleic anhydride, dicumyl peroxide and styrene is 100:3:0:0.

[0094] Comparative Example 5

[0095] The method is basically the same as Example 4, except that the mass ratio of ethylene glycol diglycidyl ether and zinc acetylacetonate to the recycled ABS material is 150:0.5:100.

[0096] Comparative Example 6

[0097] The recycled ABS material was melt blended in an internal mixer at a temperature of 190° C. and a rotation speed of 60 rpm for 18 minutes.

[0098] Table 1. Performance data of the dynamic covalent cross-linking materials provided in the embodiments of the present invention and the comparative examples

[0099] Young's modulus (MPa) Yield strength(MPa) Elongation at break (%) Example 1 1000.4±9.3 42.1±0.9 11.1±0.6 Example 2 734.8±7.1 25.2±0.7 732.8±9.9 Example 3 942.9±5.3 39.9±0.8 14.6±2.5 Example 4 1010.2±9.4 43.9±0.9 13.1±0.5 Example 5 941.9±9.3 37.1±0.8 10.0±0.6 Example 6 991.6±5.6 41.1±0.8 9.8±2.5 Example 7 751.8±7.2 26.6±0.9 767.8±9.8 Example 8 957.9±6.2 40.9±0.7 15.6±2.4 Comparative Example 1 890.3±9.2 31.2±1.2 6.5±2.5 Comparative Example 2 850.5±6.4 28.8±1.1 5.6±0.8 Comparative Example 3 783.6±8.2 27.1±0.5 7.2±1.2 Comparative Example 4 854.6±9.6 26.4±0.5 5.2±1.5 Comparative Example 5 803.6±8.0 29.1±0.6 8.2±0.8 Comparative Example 6 910.3±8.2 34.2±2.5 8.8±1.0

[0100] As shown in Table 1, compared with Example 4, the amount of initiator used in Comparative Example 1 is too small, resulting in a decrease in the amount of maleic anhydride grafted, resulting in a decrease in the Young's modulus, yield strength and elongation at break of the final material; the amount of initiator used in Comparative Example 2 is too much, which will cause the degradation of the thermoplastic polymer, resulting in a decrease in the Young's modulus, yield strength and elongation at break of the dynamic covalent cross-linked material obtained. The excessive amount of auxiliary agent used in Comparative Example 3 will increase the small molecules in the dynamic covalent cross-linked material system obtained, resulting in a decrease in the Young's modulus, yield strength and elongation at break of the dynamic covalent cross-linked material. In Comparative Example 4, because no initiator and auxiliary agent were added, the amount of maleic anhydride grafted was small, resulting in a decrease in the Young's modulus, yield strength and elongation at break of the final material. In Comparative Example 5, because the amount of cross-linking agent used was too large, the cross-linking density was too high, and the material became brittle, resulting in a decrease in the Young's modulus, yield strength and elongation at break of the final material.

[0101] Compared with Comparative Example 6 (pure ABS recycled material), the Young's modulus, yield strength and elongation at break of the dynamic covalent cross-linked materials prepared based on ABS recycled materials in Examples 1 and 4-6 of the present invention are significantly improved, among which the Young's modulus of Example 4 can be increased by 11%, the yield strength can be increased by 28%, and the elongation at break can be increased by 49%.

[0102] Application of Dynamic Covalent Cross-linked Materials Based on Thermoplastic Polymers

[0103] Example 9

[0104] The dynamic covalent cross-linked material based on ABS recycled material obtained in Example 4 and ABS were added into an internal mixer at a temperature of 190° C. and a rotation speed of 60 rpm in a ratio of 5:95 and blended for 10 minutes to obtain a thermoplastic polymer composite material (ABS / recycled material ABS dynamic cross-linked composite material).

[0105] Example 10

[0106] The dynamic covalent cross-linked material based on ABS recycled material obtained in Example 4 and ABS were added into an internal mixer at a temperature of 190° C. and a rotation speed of 60 rpm at a ratio of 10:90 and blended for 10 minutes to obtain a thermoplastic polymer composite material (ABS / recycled material ABS dynamic cross-linked composite material).

[0107] Embodiment 11

[0108] The dynamic covalent cross-linked material based on ABS recycled material obtained in Example 4 and ABS were added into an internal mixer at a temperature of 190° C. and a rotation speed of 60 rpm at a ratio of 20:80 and blended for 10 minutes to obtain a thermoplastic polymer composite material (ABS / recycled material ABS dynamic cross-linked composite material).

[0109] Example 12

[0110] The dynamic covalent cross-linked material based on ABS recycled material prepared in Example 4 and ABS were added into an internal mixer at a temperature of 190° C. and a rotation speed of 60 rpm at a ratio of 30:70 and blended for 10 minutes to obtain a thermoplastic polymer composite material (ABS / recycled material ABS dynamic cross-linked composite material).

[0111] Depend on Figure 4 It can be seen that compared with ABS, the elongation at break of the thermoplastic polymer composite material prepared by blending the dynamic covalent cross-linked material based on ABS recycled material with ABS is significantly improved.

[0112] Example 13

[0113] The dynamic covalent crosslinked material of the polypropylene material obtained in Example 8 and polypropylene were added into an internal mixer at a temperature of 190° C. and a rotation speed of 60 rpm at a ratio of 30:70 and blended for 10 minutes to obtain a thermoplastic polymer composite material (dynamic crosslinked composite material of PP / PP material).

[0114] Depend on Figure 5 It can be seen that compared with polypropylene material (PP), the elongation at break of the thermoplastic polymer composite material prepared by blending the dynamic covalent cross-linking material (PP-v) based on polypropylene with polypropylene material is also significantly improved.

[0115] Comparative Example 7

[0116] ABS was added into an internal mixer at a temperature of 190°C and a rotation speed of 60 rpm for 10 minutes.

[0117] Table 2. Performance data of thermoplastic polymer composite materials provided by the embodiments of the present invention and comparative examples

[0118]

[0119] It should be noted that the raw material mass ratio in Table 2 is the mass ratio of the thermoplastic polymer and the dynamic covalent crosslinking material based on the thermoplastic polymer. As can be seen from Table 2, compared with ABS (Comparative Example 7) and the dynamic covalent crosslinking material based on ABS recycled material (Example 4), the elongation at break of the dynamic covalent crosslinking composite material (Examples 9-12) prepared by using the dynamic covalent crosslinking material based on ABS recycled material is significantly increased, and the elongation at break can reach up to 1.78 times that of ABS and 2.1 times that of the dynamic covalent crosslinking material based on ABS recycled material.

[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a dynamic covalent cross-linked material based on thermoplastic polymer, characterized in that: The preparation method comprises the following steps: S1. A mixture comprising a thermoplastic polymer, an anhydride substance, and an initiator is first melt-blended to obtain a melt blend; S2: uniformly mixing the molten blend, the crosslinking agent and the catalyst, and performing a second melt blending to obtain a dynamic covalent crosslinking material based on a thermoplastic polymer; the crosslinking agent is a diglycidyl ether epoxide.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the acid anhydride substance to the thermoplastic polymer is 0.1 to 15:100; The mass ratio of the initiator to the thermoplastic polymer is 0.01 to 1.5:100; The mass ratio of the cross-linking agent to the thermoplastic polymer is 0.5 to 120:100; and / or The mass ratio of the catalyst to the thermoplastic polymer is 0.02 to 5:

100.

3. The preparation method according to claim 1, characterized in that: The mixture also includes an auxiliary agent; the auxiliary agent is one or more of α-methylstyrene, styrene, dimethylformamide, decene, ethyl benzoate, 2,2′-bipyridine, stearamide, dimethylacetamide, N,N-diethylcinnamic acid amide, N,N-dimethylacetamide, 3-(2-furan)acrylic acid, ethyl cinnamate, dimethylaniline, dilauryl thiodipropionate, trimethylolpropane triacrylate, 3-(2-furanyl)butyl acrylate, 3-(2-thienyl)butyl acrylate, 4,4′-diaminodiphenylmethane, cashew nut shell oil, triallyl isocyanurate, and 1,2-polybutadiene.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the auxiliary agent to the thermoplastic polymer is 0.1 to 15:

100.

5. The preparation method according to claim 1, characterized in that: The thermoplastic polymer is one or more of acrylonitrile-butadiene-styrene copolymer, styrene-butadiene-styrene copolymer, styrene-ethylene-butylene-styrene copolymer, styrene-isoprene-styrene copolymer, ethylene-vinyl acetate copolymer, polyolefin elastomer, polyethylene, polypropylene and their recycled materials; The acid anhydride substance is one or more of maleic anhydride, methyl isophthalic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, dimethyl maleic anhydride, methacrylic anhydride, itaconic anhydride, acrylic anhydride, trimellitic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride, tetrachlorophthalic anhydride, acrylic anhydride, methyltetrahydrophthalic anhydride, benzoic anhydride, 4-bromo-1,8-naphthalic anhydride, 1,8-naphthalic anhydride, 3-nitrophthalic anhydride, and tetrabromophthalic anhydride; and / or The initiator is one or more of a peroxide initiator, an azo initiator, and N,N-dimethylamine; the peroxide initiator is preferably one or more of diisopropyl peroxide, dibenzoyl peroxide, di-tert-butyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, lauroyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, methyl ethyl ketone peroxide, cyclohexanone peroxide, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, and dicyclohexyl peroxydicarbonate; the azo initiator is preferably one or more of azobisisobutyronitrile and azobisisoheptylonitrile.

6. The preparation method according to claim 1, characterized in that: The bisglycidyl ether epoxide is one or more of ethylene glycol diglycidyl ether, bisphenol A diglycidyl ether, and resorcinol diglycidyl ether; and / or The catalyst is one or more of zinc acetylacetonate, triazobicyclodecene and triphenylphosphine.

7. The preparation method according to claim 1, characterized in that: The first melt blending has a temperature of 110 to 230° C. and a time of 7 to 15 min; and / or The temperature of the second melt blending is 110-230° C., and the time is 7-15 minutes.

8. A dynamic covalent cross-linking material based on thermoplastic polymer, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the thermoplastic polymer-based dynamic covalent cross-linking material according to claim 8, characterized in that: The invention is used for preparing thermoplastic polymer composite materials. The preparation method of the thermoplastic polymer composite material comprises: mixing the dynamic covalent cross-linking material with the thermoplastic polymer, and performing a third melt blending to obtain the thermoplastic polymer composite material.

10. The use according to claim 9, characterized in that: The third melt blending has a temperature of 110 to 230° C. and a time of 7 to 15 minutes; and / or The mass ratio of the dynamic covalent cross-linking material to the thermoplastic polymer is 5-70:30-95.

Citation Information

Patent Citations

  • Dynamic covalent cross-linking material for enhancing polyethylene performance and preparation method and application thereof

    CN112358631A

  • Dynamic covalent cross-linked high-density polyethylene with high environmental stress cracking resistance and preparation method of dynamic covalent cross-linked high-density polyethylene

    CN116903795A

  • Dynamic cross-linked polymer of high-energy-storage and self-healing electric tree and preparation method of dynamic cross-linked polymer

    CN117069879A

  • Dynamically crosslinkable polymeric compositions, articles, and methods thereof

    US20230072372A1